ANALYSIS OF RESULTS AND COMPLICATIONS AFTER OPEN OPERATIONS DUE TO OCCLUSIVE-STENOTIC LESIONS OF THE MAIN ARTERIES IN THE INFRARENAL DEPARTMENT OF THE AORTA - Shaprynskyi, V.V. (World of Medicine and Biology, 2023)
The paper analyzes the efficacy of surgical treatment and its complications after open operations in patients with critical ischemia of the lower extremities due to atherosclerotic occlusive-stenotic lesions of the main arteries in the infrarenal aorta. The results of treatment in 98 (100 %) patients who were operated on by the open method were studied. Patients of the main group (43 (43.9 %)) were treated with an improved diagnostic and treatment algorithm, the risk of postoperative rethrombosis was predicted with an individual choice of reconstructive and restorative surgery, and the developed method of anastomosis formation was used. The developed approaches to treatment permitted to improve results and reduce postoperative complications from 14.54 % to 6.98 %, the number of repeated operations from 14.54 % to 4.65 %, the number of amputations from 9.09 % to 2.32 %, reduce length of patients’ stay in the hospital and reduce postoperative mortality from 7.27 % to 4.65 %. The obtained data correlate with the data of foreign colleagues, but require further long-term studies.